Olive Tree Vegetative Growth and Fruit Yield at High Air Temperatures - Campos Joedna; Lima Carla; Manuelito Maria C.; Pragana José; Ferreira Liliana; Fernandes João; Cordeiro António M.; Inês Carla F. (Journal of Horticultural Research)
In the Olive Reference Collection of Portugal, indigenous olive tree (Olea europaea L.) cultivars undergo agronomic evaluation according to the standards of the International Olive Council. Olive trees were planted in 2012 and fifteen cultivars were selected for the analysis of genotype-environment interactions regarding the correlation between annual fruit yield and annual growth of trunk perimeter with the number of days with high maximum temperatures. The cultivars showed heterogeneous development in terms of trunk perimeter, canopy, and fruit yield. Fruit yield and the number of days with maximum temperature above 35 °C were negatively correlated, especially in April–May. In spring 2022, the maximum temperature reached or exceeded 35 °C on 11 days. It was hypothesized that the development of reproductive organs and the processes of flowering or ovarian fertilization were the most affected by the unusually early occur-rence of high maximum temperatures. At the same time, vegetative growth was strongly conditioned by the limiting temperatures of photosynthesis.